2015
DOI: 10.1038/srep15322
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of neonicotinoid pesticides in food rewards impair short-term olfactory memory in foraging-age honeybees

Abstract: Neonicotinoids are often applied as systemic seed treatments to crops and have reported negative impact on pollinators when they appear in floral nectar and pollen. Recently, we found that bees in a two-choice assay prefer to consume solutions containing field-relevant doses of the neonicotinoid pesticides, imidacloprid (IMD) and thiamethoxam (TMX), to sucrose alone. This suggests that neonicotinoids enhance the rewarding properties of sucrose and that low, acute doses could improve learning and memory in bees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 38 publications
5
49
0
Order By: Relevance
“…Both neonicotinoid insecticides and parasites alter associative learning and cognitive functions of bees [5][6][7][8][9]. Acting as nicotinic acetylcholine receptor (nAChR) agonists [10], exposure to very low levels of neonicotinoids can disrupt normal function of neurons in the bee brain [11,12] and lead to disruptions in learning and memory [8,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both neonicotinoid insecticides and parasites alter associative learning and cognitive functions of bees [5][6][7][8][9]. Acting as nicotinic acetylcholine receptor (nAChR) agonists [10], exposure to very low levels of neonicotinoids can disrupt normal function of neurons in the bee brain [11,12] and lead to disruptions in learning and memory [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…[8,9,24,25] whereas potential impacts on other pollinators such as bumblebees are as yet poorly known [13,26]. In addition to honeybees, bumblebees play a major role in providing pollinating services to wild and crop plants [27].…”
Section: Introductionmentioning
confidence: 99%
“…Various modifications in honeybee behaviour, which seem to be associated with cognitive impairment, have been described. General motion56, waggle dancing7, homing flights8910, and olfactory learning and memory11121314 were shown to be disrupted by chronic and acute treatment with various neonicotinoids at doses comparable to those experienced by animals in the field.…”
mentioning
confidence: 99%
“…Imidacloprid has been shown to impair olfactory learning and memory in a number of studies111314232425. As revealed by in vivo electrophysiological recordings, imidacloprid application produces a tonic inward current in Kenyon cells of the MBs, making them unresponsive to acetylcholine.…”
mentioning
confidence: 99%
“…In another study, evidence for clear impacts on learning and memory were observed upon exposure of honey bees to dietary imidacloprid resulting in a dose of 1.2 ng/bee (estimates based on consumption rates) using the PER assay (Williamson and Wright, 2013). Similarly, honey bees that were fed sucrose solution containing 10 nM imidacloprid or 1 nM thiamethoxam exhibited impaired olfactory learning and short-term memory, as evaluated using the PER (Wright et al, 2015).…”
Section: Consideration Of Biological Plausibility and Empirical Supportmentioning
confidence: 97%